2016
DOI: 10.5664/jcsm.5670
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Motor Vehicle Driver Positive Airway Pressure Therapy Adherence in a Sleep Center

Abstract: Study Objectives: To assess positive airway pressure (PAP) therapy adherence in commercial motor vehicle (CMV) drivers presenting to a sleep center. Methods: A retrospective chart review of 120 drivers evaluated for obstructive sleep apnea OSA and 53 initiated on PAP therapy in a single sleep center over a one-year period (2012); PAP therapy data were collected up to 1 year. Results: Early PAP usage best predicted adherence up to 1 year (p < 0.0001) compared to patient factors, OSA disease characteristics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Multiple studies, however, have shown correlation between adherence from as early as 3-7 days with later adherence at 1, 3, and 6 months, and 1 year. 23,[40][41][42] Finally, although we identified an association between black race and PAP adherence, the retrospective study design did not allow us to determine the basis for the observed relationship. Studies have shown a higher prevalence of insomnia and short sleep duration among black adults, 43,44 and it is unknown if these factors or other confounders explain the racial disparity that was seen.…”
Section: Discussionmentioning
confidence: 84%
“…Multiple studies, however, have shown correlation between adherence from as early as 3-7 days with later adherence at 1, 3, and 6 months, and 1 year. 23,[40][41][42] Finally, although we identified an association between black race and PAP adherence, the retrospective study design did not allow us to determine the basis for the observed relationship. Studies have shown a higher prevalence of insomnia and short sleep duration among black adults, 43,44 and it is unknown if these factors or other confounders explain the racial disparity that was seen.…”
Section: Discussionmentioning
confidence: 84%
“…In another cohort study focusing on the relationship between pre­treatment sleep schedule regularity and PAP adherence [25], Sawyer et al did not identify significant black-white differences in frequency of one month treatment adherence (within-group % ≥ 4 hrs daily adherence, 83% [black] vs 60% [white]; p=0.40 ). Similarly, Colvin et al did not identify significant race-ethnic PAP use differences in a study of individuals referred to a sleep center for commercial motor vehicle driver evaluations [35], though this sample may not be reflective of general clinical sleep center populations. In this study, blacks had non-significant (p = 0.11) higher frequency of adequate PAP adherence (≥ 4 hrs daily on ≥ 70% days) than whites at one week (72% vs 28%), 1 month (74% vs 27%), 3 months (70% vs 30%), and 12 months (76% vs 24%).…”
Section: Resultsmentioning
confidence: 99%